PENGARUH KEGIATAN PRAKTIKUM TERHADAP KEMAMPUAN KOGNITIF PESERTA DIDIK KELAS XI SMA NEGERI 5 METRO - Sri Arum Mawarni; Dedy Hidayatullah Alarifin; Eko Prihandono (JURNAL FIRNAS, 2024)
Practical activities will make students excited about learning so that cognitive abilities will be good. Practical activities make it easier for teachers to make abstract learning realistic and students will be in a pleasant learning condition. In minimizing abstract concepts in physics learning into real concepts, then one of the materials that can be found in everyday life is elasticity. This study aims to determine the effect of practicum activities on students' cognitive abilities after using elasticity practicum tools. The type of research used is quasi experimental design with nonequivalent control group design. The population in this study were students of class XI IPA SMA Negeri 5 Metro. The sampling technique used simple random sampling, obtained XI IPA 2 and XI IPA 4 classes as research samples. The instrument used to determine the cognitive abilities of students is a test question. The results of hypothesis testing measured using the Wilcoxon Signed Rank test nonparametric test showed that the Sig. (2-tailed) value of 0.000 <0.05 so that H0 was rejected. The results showed that there was an effect of practicum activities on students' cognitive abilities.